Alunos do ensino médio e a generalização de padrão - Perez, Elisangela Parra Zigart (2006)
Several Mathematics researchers have been emphasizing the importance of the work with the observation and standard generalization in the development of the algebraic thought. The same opinion was also accepted in the High School National Parameters in 1998. This fact took me to carry out a research here described in which I investigate if and how High School students solve problematic situations that involve standard of generalization. It was elaborated five activities to collect data and one of them was based on a research done by Lesley Lee. The other ones were created and analyzed based on authors such as John Mason, Vale & Pimentel and Fiorentini, Miorin and Miguel. Those activities were applied during two sessions to nine High School students of the first three grades of state school in the interior of São Paulo, near Campinas. The final results drew the conclusion that although the students alleged they have never worked with that ind of activity before, not only they solved them but also used a lot of strategies to solve them